2002
DOI: 10.1007/s00256-002-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of Osgood-Schlatter disease: the course of the disease

Abstract: We clarified the progress of OSD with MRI. The process of OSD started from the apophyseal stage and a tear appeared in the secondary ossification center, widening to an opened shell-like shape. This damage progressed to an ossicle in some cases. In short, the ossicle was formed from an avulsed portion. It was very difficult to show the course of OSD with radiography. MR images were especially useful for revealing early and progressive lesions of OSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 8 publications
3
84
1
Order By: Relevance
“…The results concerning quadriceps femoris muscle tightness were consistent with those of earlier reports [3]. OSD is a traction apophysitis of the tibial tubercle caused by overload/microfractures in the attachment of the patellar tendon [1,8]. The repetitive strain, in turn, is caused by the strong pull produced by the quadriceps femoris muscle during sporting activities.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results concerning quadriceps femoris muscle tightness were consistent with those of earlier reports [3]. OSD is a traction apophysitis of the tibial tubercle caused by overload/microfractures in the attachment of the patellar tendon [1,8]. The repetitive strain, in turn, is caused by the strong pull produced by the quadriceps femoris muscle during sporting activities.…”
Section: Discussionsupporting
confidence: 81%
“…Ultrasonography is useful for the visualization of orthopedic conditions, especially soft tissue diseases, and it is particularly effective in the early diagnosis of OSD [16]. Early detection of OSD and conservative treatment can enable an early return to sporting activities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…5 Improvement in patellar tendinosis was demonstrated in those that became asymptomatic, despite persistence of nonunion ossicles. 5 Hirano et al, 6 in another sequential MRI study, found that a partial tear of the secondary ossification center was in place before patellar tendon swelling but agreed that symptom resolution likely follows the resolution of tendon changes. Thus, although repeated microavulsion fractures may be the first radiographic finding and contribute to OSD pain and pathology, 6 they do not seem to be the primary source of pain and dysfunction.…”
mentioning
confidence: 99%
“…5 Hirano et al, 6 in another sequential MRI study, found that a partial tear of the secondary ossification center was in place before patellar tendon swelling but agreed that symptom resolution likely follows the resolution of tendon changes. Thus, although repeated microavulsion fractures may be the first radiographic finding and contribute to OSD pain and pathology, 6 they do not seem to be the primary source of pain and dysfunction. 5,6 Recent MRI and ultrasound reports are also consistent with a description of OSD as "a tendinopathy/ apophysosis of the patellar tendon/tibial tubercle."…”
mentioning
confidence: 99%
See 1 more Smart Citation